BURDEN OF KLEBSIELLA PNEUMONIAE AND ESCHERICHIA COLI ISOLATES THAT PRODUCE EXTENDED-SPECTRUM BETA-LACTAMASES AT THE TERTIARY CARE HOSPITAL IN UTTAR PRADESH, LUCKNOW - MISHRA, NEETI; KUMARI, DAYAVANTI; TIWARI, KHYATI (International Journal of Pharmacy and Pharmaceutical Sciences, 2025)
Objective: To ascertain the prevalence of Escherichia coli isolates and Klebsiella pneumoniae that generates Extended-Spectrum Beta-Lactamases (ESBLs) in the tertiary care hospital in Lucknow, Uttar Pradesh. Methods: Screening tests have been developed by the Clinical Laboratory Standard Institute (CLSI) to identify the Klebsiellla pneumoniae and Escherichia coli that generate ESBLs. Finally, performing combination disk test on probable ESBL-producing isolates, ESBL phenotypic confirmation was established. Results: 94 (62.7%) of the 150 ESBL-positive isolates were female, while 56 (37.3%) were male. The largest concentration of E. coli which was positive for ESBL production was from urine, and it also shows the lowest concentrations coming from sputum, blood, and CSF samples and the largest concentration of ESBL-positive Klebsiella pneumoniae was found in sputum, followed by urine, pus, and blood, while the lowest concentration was found in a CSF sample. E. coli had 158 of the 267 isolates, and of them, 80 were ESBL positive. Similarly, 70 of the 109 Klebsiella pneumoniae isolates tested were ESBL positive. Conclusion: E. coli had an ESBL prevalence of 53.34% in the current study, while K. pneumoniae had 46.7% prevalence. Klebsiella pneumoniae and Escherichia coli that produce ESBLs were found in relatively high numbers in the urine, sputum, pus, ET aspirate, and blood samples. The doctors must follow stringent infection control procedures at the hospital and judicious antimicrobial usage guidelines.